2021
DOI: 10.1177/0162643421989970
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Technology Supports on Community Grocery Shopping Skills for Students With Intellectual and Developmental Disabilities: A Meta-Analysis

Abstract: In this meta-analytic review, we investigated the effects of technology supports on the acquisition of shopping skills for students with intellectual and developmental disabilities (IDD) between the ages of 5 and 24. Nineteen single-case experimental research studies, presented in 15 research articles, met the current study’s inclusion criteria and the What Works Clearinghouse (WWC) standards. An analysis of potential moderators was conducted, and we calculated effect sizes using Tau-U to examine the impact of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 47 publications
(80 reference statements)
0
4
0
Order By: Relevance
“…As shown by the red colour of the citation network, Parette and Wojcik's (2004) work was directly cited by Sánchez and Llera (2007). The network in green highlights that Yakubova and Taber-Doughty's (2013) paper was directly cited by several scholars (Collins et al, 2014;Jung et al, 2022;Morash-Macneil et al, 2018;Park et al, 2019). Multiple authors had the most co-citations during the period from 2006 to 2015 (Izzo et al, 2009;Michaels & McDermott, 2003;Okolo & Bouck, 2007;Okolo & Diedrich, 2014;Quinn et al, 2009;Stetter & Hughes, 2010;Twyman & Tindal, 2006).…”
Section: Intellectual Structure Analysismentioning
confidence: 97%
“…As shown by the red colour of the citation network, Parette and Wojcik's (2004) work was directly cited by Sánchez and Llera (2007). The network in green highlights that Yakubova and Taber-Doughty's (2013) paper was directly cited by several scholars (Collins et al, 2014;Jung et al, 2022;Morash-Macneil et al, 2018;Park et al, 2019). Multiple authors had the most co-citations during the period from 2006 to 2015 (Izzo et al, 2009;Michaels & McDermott, 2003;Okolo & Bouck, 2007;Okolo & Diedrich, 2014;Quinn et al, 2009;Stetter & Hughes, 2010;Twyman & Tindal, 2006).…”
Section: Intellectual Structure Analysismentioning
confidence: 97%
“…Insights from interviews and surveys have shown that the use of information and communication technologies, and mobile devices in particular, has become widespread among adults with IDs (Ramsten et al, 2018), and may even have significant personal and social benefits (Chadwick et al, 2018;Martin et al, 2021). Use of technology has also been found to be beneficial for people with IDs in education (Maebara et al, 2022) and the development of skills in daily life (Jung et al, 2021), particularly due to the variety of modalities (text, images, video, audio, etc. ) supported by the devices.…”
Section: Usage Of Technology By People With Idmentioning
confidence: 99%
“…The Effects of Technology Supports on Community Grocery Shopping Skills for Students With Intellectual and Developmental Disabilities: A Meta-Analysis [44] The paper examines the impact of traditional technologies that are used during occupational therapy of young people with IDD.…”
Section: An Overview Of Previous Researchmentioning
confidence: 99%